1982
DOI: 10.1530/acta.0.1010348
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism following subacute thyroiditis

Abstract: The occurrence of permanent overt or subclinical hypothyroidism following subacute thyroiditis (SAT) was studied in 32 patients during 0.75\p=n-\13 years (mean 4.2 years) of follow-up. Permanent hypothyroidism developed in 2 patients in whom a characteristic feature was persistence of circulating thyroid antibodies in high titres from the onset of SAT indicating the presence of autoimmune thyroiditis. One also showed cytological evidence of autoimmune thyroiditis. In another patient subclinical hypothyroidism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

1986
1986
1999
1999

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 16 publications
1
17
1
Order By: Relevance
“…The more frequent reaction to the peptide of 80 kDa in patients with subacute thyroiditis does not indicate a pathogenic role but rather seems to represent an epiphenomenon, since follicular destruction and cell death probably release not only thyroglobulin, but also endoproteases and peptides produced by their action. Many authors have reported the development of Hashimotos thyroiditis after subacute thyroiditis (25)(26)(27)(28). It would be interesting to determine the repertoire of antithyroglobulin antibodies in these patients in order to elucidate some of the immune mechanisms involved or to identify a subtype of antithyroglobulin antibody.…”
Section: Discussionmentioning
confidence: 99%
“…The more frequent reaction to the peptide of 80 kDa in patients with subacute thyroiditis does not indicate a pathogenic role but rather seems to represent an epiphenomenon, since follicular destruction and cell death probably release not only thyroglobulin, but also endoproteases and peptides produced by their action. Many authors have reported the development of Hashimotos thyroiditis after subacute thyroiditis (25)(26)(27)(28). It would be interesting to determine the repertoire of antithyroglobulin antibodies in these patients in order to elucidate some of the immune mechanisms involved or to identify a subtype of antithyroglobulin antibody.…”
Section: Discussionmentioning
confidence: 99%
“…The initial presentation with fever and extreme thyroid tenderness indicated subacute thyroiditis, but the normal erythrocyte sedimentation rate and the radioisotope studies refuted that diagnosis. Subacute thyroiditis frequently has a phase of hyperthyroidism [5,6], but is associated with a low uptake of radioiodide and a non-diffuse pattern of distribution of the consumed isotope [5]. Autoimmune thyroiditis, clinically seen as either Hashimoto disease with or without hypothyroidism or Graves disease with hyperthyroidism, may rarely follow an episode of subacute thyroiditis [4,5,7].…”
Section: Discussionmentioning
confidence: 99%
“…Subacute thyroiditis frequently has a phase of hyperthyroidism [5,6], but is associated with a low uptake of radioiodide and a non-diffuse pattern of distribution of the consumed isotope [5]. Autoimmune thyroiditis, clinically seen as either Hashimoto disease with or without hypothyroidism or Graves disease with hyperthyroidism, may rarely follow an episode of subacute thyroiditis [4,5,7]. However, with subsequent Graves disease, there is a defined time interval between the development of a painful thyroid and the hyperthyroidism [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations